DEMARKETING POLITICALLY IMPOSED CANDIDATES: A PATHWAY TO GENUINE DEMOCRACY IN NIGERIA (UNIZIK Journal of Marketing, 2026)
This study, titled Demarketing Politically Imposed Candidates: A Pathway to Genuine Democracy in Nigeria, examined the application of demarketing within the political context, with particular focus on its effects on electoral integrity, voter trust, and political accountability, as well as the mediating role of voter political awareness. A quantitative survey research design was adopted. Data were collected through a structured questionnaire administered via Google Forms, yielding 262 valid responses from Nigerian voters. The instrument employed a four-point Likert scale ranging from strongly disagree to strongly agree in order to eliminate neutral responses and encourage clearer opinion expression. Data were analyzed using descriptive statistics, analysis of variance (ANOVA), and Partial Least Squares Structural Equation Modeling (PLS-SEM) implemented through SmartPLS, with measurement and structural model assessments confirming reliability, validity, and acceptable model fit. The findings revealed that demarketing politically imposed candidates significantly enhances voter trust and political accountability but does not exert a significant direct effect on electoral integrity. Furthermore, the results indicated that voter political awareness significantly mediates the relationship between demarketing politically imposed candidates and democratic outcomes. The study concluded that demarketing politically imposed candidates represents a viable political marketing approach for strengthening democratic participation and accountability in Nigeria. Accordingly, the study recommended intensified voter education programmes, more transparent political party nomination processes, and stronger civil society advocacy aimed at discouraging candidate imposition.
Keywords: Demarketing, Genuine Democracy, Electoral Integrity, Voter Trust & Political Accountability.